Multiple Orbitoides d'Orbigny lineages in the Maastrichtian? Data from the Central Sakarya Basin (Turkey) and Arabian Platform successions (Southeastern Turkey and Oman) - Ozcan, Ercan; Yucel, Ali Osman; Catanzariti, Rita; Kaygili, Sibel; Okay, Aral I.; Simmons, Michael D.; Erbil, Umitcan (Springer Int Publ Ag, 2021)
The standard reconstruction of species of Orbitoides d'Orbigny into a single lineage during the late Santonian to the end of the Maastrichtian is based upon morphometric data from Western Europe. An irreversible increase in the size of the embryonic apparatus, and the formation of a greater number of epi-embryonic chamberlets (EPC) with time, is regarded as the main evolutionary trends used in species discrimination. However, data from Maastrichtian Orbitoides assemblages from Central Turkey and the Arabian Platform margin (Southeastern Turkey and Oman) are not consistent with this record. The Maastrichtian Besni Formation of the Arabian Platform margin in Southeastern Turkey yields invariably biconvex specimens, with small, tri- to quadrilocular embryons and a small number of EPC, comparable to late Campanian Orbitoides medius (d'Archiac). The upper Maastrichtian Tarakli Formation from the Sakarya Basin of Central Turkey contains two distinct, yet closely associated forms of Orbitoides, easily differentiated by both external and internal features. Flat to biconcave specimens possess a small, tri- to quadrilocular embryonic apparatus of Orbitoides medius-type and a small number of EPC, whereas biconvex specimens possess a large, predominantly bilocular embryonic apparatus, and were assigned to Orbitoides ex. interc. gruenbachensis Papp-apiculatus Schlumberger based on morphometry. The flat to biconcave specimens belong to a long overlooked species Orbitoides pamiri Meric, originally described from the late Maastrichtian of the Tauride Mountains in SW Turkey. This species is herein interpreted to be an offshoot from the main Orbitoides lineage during the Maastrichtian, as are forms that we term Orbitoides 'medius', since they recall this species, yet are younger than normal occurrence with the accepted morphometrically defined lineage. The consistent correlation between the external and internal test features in O. pamiri implies that the shape of the test is not an ecophenotypic variation, but appears to be biologically controlled. We, therefore, postulate that more than one lineage of Orbitoides exists during the Maastrichtian, with a lineage that includes O. 'medius' and O. pamiri displaying retrograde evolutionary features.
Keywords: Orbitoides; Maastrichtian; Morphometry; Central Sakarya Basin; Arabian Platform margin; Turkey